Quality Assurance and its Impact on Academic Performance at Department of Pharmaceutical Sciences, University of Tripoli Alahlia - Ahmed Abired,; Alaeddin Ejled,; Tawfig abduala,; Fathi Abusaa, (AlQalam Journal of Medical and Applied Sciences, 2024)
With its establishment in 1999, University of Tripoli Alahia (UTA) has been incorporating the system of quality assurance and accreditation into its strategic plan and has occupied it as an essential tool to achieve its vision, mission and objectives. UTA has obtained the institutional accreditation of the National Center for Quality Assurance and Accreditation in 2008, and then it also obtained the academic accreditation in 2011. Pharmaceutical Sciences (PSs) Department is one of eight departments included inside the university, PSs Department has obtained the academic accreditation in 2019, and as part of its strategic planning to enhance the quality of education, new commitments and requirements have been imposed to enhance teaching, learning and research quality and productivity. Thus, this study aims at identifying the role of quality assurance in improving the academic performance at the PSs Department under study. The areas are ranged from teaching and learning to research quality and productivity. The paper will outline the level of achievements made, specify the challenges, and provide necessary recommendations. The results demonstrate that the application of the quality assurance process has resulted in an important improvement in the running process of teaching, learning and researching at the PSs Department. The study employs a qualitative content analysis and the results are supported by a survey questionnaire and interviews conducted with the PSs Department teaching staff. منذ إنشائها عام 1999، قامت جامعة طرابلس الأهلية بدمج نظام ضمان الجودة والاعتماد في خطتها الاستراتيجية واتخذته أداة أساسية لتحقيق رؤيتها ورسالتها وأهدافها. حصلت جامعة طرابلس الأهلية على الاعتماد المؤسسي من المركز الوطني لضمان الجودة والاعتماد عام 2008، ثم حصلت أيضًا على الاعتماد الأكاديمي عام 2011. قسم العلوم الصيدلانية هو أحد الأقسام الثمانية المتضمنة داخل الجامعة، وقد حصل قسم العلوم الصيدلانية على الاعتماد الأكاديمي عام 2019، وكجزء من تخطيطه الاستراتيجي لتعزيز جودة التعليم، تم فرض التزامات ومتطلبات جديدة لتعزيز جودة وإنتاجية التدريس والتعلم والبحث. وبالتالي، تهدف هذه الدراسة إلى تحديد دور ضمان الجودة في تحسين الأداء الأكاديمي في قسم العلوم الصيدلانية قيد الدراسة. وتتراوح المجالات من التدريس والتعلم إلى جودة وإنتاجية البحث. وستوضح الورقة مستوى الإنجازات التي تحققت، وتحدد التحديات، وتقدم التوصيات اللازمة. وتوضح النتائج أن تطبيق عملية ضمان الجودة أدى إلى تحسن مهم في سير عملية التدريس والتعلم والبحث في قسم العلوم الاجتماعية. وتستخدم الدراسة تحليلاً نوعياً للمحتوى وتدعم النتائج استبيان مسح ومقابلات أجريت مع أعضاء هيئة التدريس في قسم العلوم الاجتماعية.